Impacts of Outdoor Environmental Education on Teacher Reports of Attention, Behavior, and Learning Outcomes for Students With Emotional, Cognitive, and Behavioral Disabilities - Szczytko, Rachel; Carrier, Sarah J.; Stevenson, Kathryn T. (Frontiers in Education, 2018)
There are over 4 million students with reported emotional, cognitive, and behavioral disabilities (ECBD) in the United States. Teachers most frequently situate instruction inside, however, outdoor environmental education (EE) can improve academic and affective outcomes for many students, including students with ECBD. In North Carolina, U.S.A., an EE program utilizes outdoor science instruction for fifth-grade students. The program takes place over four to 10 full-school days across the year, and instruction occurs in both schoolyards and natural areas. The program aligns outdoor EE with state and national science education standards. Using a quasi-experimental design, the present study examined the impacts of the program on indicators of ECBD (e.g., student behavior, attention span), science efficacy, nature of science, and academic achievement for students with ECBD. We measured these factors using online surveys from both students identified with ECBD and their classroom teachers, as well as students with ECBD from matched control schools and their respective teachers. Students in both treatment (n = 99) and control (n = 62) classrooms took the survey two times over the school year. Quantitative data revealed teachers perceived students had significantly improved attention spans and decreased disruptive behaviors when learning outdoors. Students in the treatment group maintained measures of nature of science, science efficacy and science grades, keeping in line with their peers in the control group. We supplemented survey data with teacher interview data about their impressions of the outdoor program and the experiences of their students identified with ECBD. Teacher interview responses supported quantitative findings. These findings indicate that outdoor EE has the potential to be at least as effective a method for science instruction as classroom teaching, and in the case of addressing indicators of ECBD, outdoor EE may be a successful strategy for student learning.